2007
DOI: 10.1111/j.1530-0277.2006.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

The Alcohol Use Disorders Identification Test: An Update of Research Findings

Abstract: Background: The Alcohol Use Disorders Identification Test (AUDIT) has been extensively researched to determine its capability to accurately and practically screen for alcohol problems.Methods: During the 5 years since our previous review of the literature, a large number of additional studies have been published on the AUDIT, abbreviated versions of it, its psychometric properties, and the applicability of the AUDIT for a diverse array of populations. The current article summarizes new findings and integrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
922
3
23

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,201 publications
(986 citation statements)
references
References 90 publications
18
922
3
23
Order By: Relevance
“…Der maximale AUDIT-C-Summenwert beträgt 12. Risikokonsum besteht bei einem Wert von >3 bei Frauen und >4 bei Männern [23,24]. Rauschkonsum lag anhand der dritten Frage vor, wenn jemand 6 oder mehr alkoholische Getränke bei einer Gelegenheit, mindestens einmal im Monat oder häufiger getrunken hat.…”
Section: Methodenunclassified
“…Der maximale AUDIT-C-Summenwert beträgt 12. Risikokonsum besteht bei einem Wert von >3 bei Frauen und >4 bei Männern [23,24]. Rauschkonsum lag anhand der dritten Frage vor, wenn jemand 6 oder mehr alkoholische Getränke bei einer Gelegenheit, mindestens einmal im Monat oder häufiger getrunken hat.…”
Section: Methodenunclassified
“…Data included vital signs (i.e. blood pressure and body mass index), selected laboratory values (CD4 count, HIV viral load, lipids, blood glucose, and glycosylated hemoglobin), vaccinations received, and results from screenings routinely performed during CBOC visits [alcohol use by Alcohol Use Disorder Identification Test-Consumption (AUDIT-C) questions, 5 depression screening using the Patient Health Questionnaire, 6 and tobacco screening and cessation counseling].…”
Section: The Tcc Interventionmentioning
confidence: 99%
“…‡The AUDIT-C consists of the three consumption questions in the original AUDIT screening instrument and is aimed at identifying risky drinking. These figures represent the percentage of individuals assessed as having risky alcohol consumption on the basis of the limits of 4 for girls and 5 for boys in the AUDIT-C (35) §The term primary drug refers to the drug that causes the adolescent the most problems at the start of treatment (36) A total of 21% of the adolescents reported that they had been exposed to two different forms of violence or abuse, and 8% reported three forms. Gender differences are apparent here, with 24% of girls having been exposed to all three forms of violence or abuse as compared with only 1% of boys.…”
Section: Resultsmentioning
confidence: 99%